Analisis Metode Pengakuan Pendapatan Proyek Embangunan Terminal Container Ct-3 Dalam Rangka Penyajian Laporan Keuangan PT. Andesmont Sakti - Abdul Gafar; Zulkifli Umar (Asosiasi Dosen dan Praktisi Ekonomi Nusantara, 2025)
This study aims to analyze the implementation of revenue recognition methods in construction contracts at PT. Andesmont Sakti and to examine their compliance with Statement of Financial Accounting Standards (PSAK) No. 34 on Construction Contracts. The research employs a qualitative method using a case study approach. Data were collected through the analysis of financial statements, project performance reports, and interviews with personnel from the finance and operational divisions. The results indicate that PT. Andesmont Sakti applies the percentage-of-completion method using a physical progress approach in recognizing construction contract revenue. Revenue recognition is based on the approved level of physical project completion as documented in the Project Performance Report and is recorded upon the issuance of invoices to clients. Although the company acknowledges the cost-to-cost approach as stipulated in PSAK No. 34, the physical progress method is preferred in practice as it is considered to better reflect the actual conditions of project execution in the field. Overall, the revenue and expense recognition practices at PT. Andesmont Sakti are in accordance with PSAK No. 34, particularly with respect to revenue recognition based on the stage of contract completion, thereby ensuring that the financial statements provide reliable and relevant information for stakeholders.